Parental RNA interference of genes involved in embryonic development of the western corn rootworm, Diabrotica virgifera virgifera LeConte. (August 2015) - Khajuria, Chitvan; Vélez, Ana M.; Rangasamy, Murugesan; Wang, Haichuan; Fishilevich, Elane; Frey, Meghan L.F.; Carneiro, Newton Portilho; Gandra, Premchand; Narva, Kenneth E.; Siegfried, Blair D.
Abstract: RNA interference (RNAi) is being developed as a potential tool for insect pest management and one of the most likely target pest species for transgenic plants that express double stranded RNA (dsRNA) is the western corn rootworm. Thus far, most genes proposed as targets for RNAi in rootworm cause lethality in the larval stage. In this study, we describe RNAi-mediated knockdown of two developmental genes, hunchback ( hb ) and brahma ( brm ), in the western corn rootworm delivered via dsRNA fed to adult females. dsRNA feeding caused a significant decrease in hb and brm transcripts in the adult females. Although total oviposition was not significantly affected, there was almost complete absence of hatching in the eggs collected from females exposed to dsRNA for either gene. These results confirm that RNAi is systemic in nature for western corn rootworms. These results also indicate that hunchback and brahma play important roles in rootworm embryonic development and could provide useful RNAi targets in adult rootworms to prevent crop injury by impacting the population of larval progeny of exposed adults. The ability to deliver dsRNA in a trans-generational manner by feeding to adult rootworms may offer an additional approach to utilizing RNAi for rootworm pest management. The potential to develop parental RNAi technology targeting progeny of adult rootworms in combination with Bt proteins or dsRNA lethal to larvae may increase opportunities to develop sustainable approaches to rootworm management involving RNAi technologies for rootworm control. Graphical abstract: Highlights: Exposure of WCR females hb and brm dsRNA via feeding exhibited knockdown and absence of egg hatching. This study demonstrates for the first time parental RNAi in WCR. hb and brm could be useful in WCR management to prevent crop injury by impacting the next generation. These results may extend to other parental RNAi genes in WCR and other insect pests as a new approach to insect control.